Case Report: Cryptococcal eosinophilic meningitis in a patient with Hodgkin lymphoma - Zhang, Fang; Li, Yuchen; Shen, Huijun; Tao, Jie; Wang, Jie (Frontiers in Neurology, 2022)
Cryptococcal meningitis is the most common fungal meningitis in clinical practice. It primarily occurs in immunocompromised people and is typically associated with human immunodeficiency virus (HIV) infection. In rare cases, it is associated with Hodgkin lymphoma (HL). Eosinophilic meningitis (EM) is characterized by increased eosinophils in the cerebrospinal fluid (CSF) and is often caused by a parasitic infection of the central nervous system (CNS). EM caused by cryptococcal infection is rare; only four cases have been reported in the past 30 years. Here, we report a case of cryptococcal meningitis in a patient with HL who presented with an atypical eosinophil-predominant CSF cytology response. The patient's eosinophil proportion reached 91%; a proportion this high has not been reported previously and may be associated with HL. After antifungal therapy and tumor chemotherapy, the proportion of eosinophils decreased significantly. This case shows that cryptococcal meningitis and HL may be simultaneously contributing to CSF eosinophilia. HL should be considered in patients with eosinophilic cryptococcal meningitis and multiple adenopathies.